Minimally Invasive Mitral Valve Surgery: Initial One-team Experience and Short Review. - Selman Dumani; Ermal Likaj; Laureta Dibra; Saimir Kuci; Edlira Rruci; Alfred Ibrahimi; Aferdita Veseli; Fjorba Mana; Devis Pellumbi; Alessia Mehmeti; Ali Refatllari; Altin Veshti (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Minimally invasive mitral valve surgery (MIMVS) is now a widely accepted and more frequently utilized method for patients needing mitral valve surgery. The promoted advantages are less trauma, less bleeding, less pain, and fewer wound infections, allowing faster postoperative and decreased healthcare costs.